Expression of BACE1 in the Rat Carotid Body - Li, Chaohong; Zhao, Baosheng; Fan, Ya-nan; Jia, Xianglei; Liu, Yuzhen (Frontiers in Physiology, 2020)
This study explored the expression of BACE1 (β-amyloid precursor protein cleaving enzyme 1) in the rat carotid body and the effect of CIH (cyclic intermittent hypoxia) on the expression of BACE1. We found that BACE1 was expressed in the rat carotid body and located in the nerve endings and type II cells but not in type I cells. CIH reduced BACE1 level in the carotid body, and reoxygenation or ROS scavenger alleviated this reduction. Furthermore, we found that CIH augmented the mRNA level of PGC-1α but attenuated the mRNA level of BACE1 in the carotid body. Taken together, our results suggest that CIH promotes the production of ROS that upregulates the level of PGC-1α, which may in turn inhibits the transcription of BACE1, and that a reduction in the BACE1 level may be related to CIH-induced reversible and ROS-dependent carotid body plasticity. Our study provides a new candidate molecule for further study of the mechanism of carotid body plasticity.